Does culture matter? Corporate reputation and sustainable satisfaction in the Chinese and German banking sector - Svenja Damberg; Yide Liu; Christian M. Ringle (Journal of Marketing Analytics, 2023)
Corporate reputation is important for all types of banks across the world, despite these countries differing culturally. Building on an extended corporate reputation model, we identify the key drivers of customer-based reputation and sustainable customer satisfaction in two culturally different countries, namely China and Germany. We also consider two reputation dimensions—perceived competence and likeability—and their effects on the target construct. Empirical data from 625 German and 734 Chinese commercial bank customers allow us to estimate the corporate reputation model with the partial least squares structural equation modeling (PLS-SEM) method, and by substantiating the relationships by means of a necessary condition analysis (NCA) and a predictive power analysis. By comparing the two countries' results, we identify their cultural differences. Overall, we confirm the model's relevance for the two cultures, finding that banks' perceived attractiveness is the most important driver of both cultures' customer-perceived bank reputation. By means of an importance-performance map analysis, we identify a large overlap between the two cultures' set of important constructs, likeability's much greater importance in Germany, and the perceived quality construct's relevance in both countries. We contribute to research and scientific knowledge about corporate reputation models by identifying the similarities in and differences between two countries' markets with respect to the banking sector, all of which have implications for international banks' management.
Keywords: 650; Customer-perceived reputation; Sustainable satisfaction; Commercial banks; PLS-SEM